2008
DOI: 10.1016/j.jss.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Depletion Causes a Fatal Defect in Murine Pulmonary Staphylococcus aureus clearance

Abstract: Background-Staphylococcus aureus is the most common cause of healthcare-associated pneumonia. Despite the significant morbidity and mortality associated with the disease, animal models of S. aureus pneumonia are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 37 publications
(24 reference statements)
2
75
0
1
Order By: Relevance
“…As a successful human pathogen, S. aureus has evolved many mechanisms to counteract neutrophils (9). While neutrophils are absolutely necessary for the eradication of staphylococcal infections (68,69), their presence during infection has also been described as pathogenic (66,70). IP-10, which we showed to be upregulated systemically by SEA, can promote phagocytosis (71); however, MIP-2, which is also upregulated, is capable of enhancing intracellular bacterial survival within neutrophils (66,70).…”
Section: Discussionmentioning
confidence: 94%
“…As a successful human pathogen, S. aureus has evolved many mechanisms to counteract neutrophils (9). While neutrophils are absolutely necessary for the eradication of staphylococcal infections (68,69), their presence during infection has also been described as pathogenic (66,70). IP-10, which we showed to be upregulated systemically by SEA, can promote phagocytosis (71); however, MIP-2, which is also upregulated, is capable of enhancing intracellular bacterial survival within neutrophils (66,70).…”
Section: Discussionmentioning
confidence: 94%
“…aureus causes an especially severe pneumonia, marked by an intense proinflammatory response that interferes with respiration and causes excessive mortality (15). While PMNs are required to effect bacterial clearance (19), accumulating data suggest that the regulation of PMN recruitment and their activation status may be critical in determining the outcome of the S. aureus infection (17,18). In our studies, significantly increased mortality was observed in clodronate-treated mice; these mice had an increased DC population, increased CXCR3 ligand expression, and increased CD4 ϩ population, as well as decreased macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…PMNs have long been thought to be critical for efficient staphylococcal clearance (19,22), and the increased incidence of severe staphylococcal infection in humans with disorders of PMN function or activation, such as chronic granulomatous disease (10, 12), confirm this observation. PMNs themselves can also contribute to the pathology associated with staphylococcal infection.…”
mentioning
confidence: 93%
“…Circulating neutrophils are recruited rapidly to infectious areas through chemotactic signals and eliminate bacteria by bactericidal and phagocytic mechanisms [2,3,26] . Depletion of neutrophils delays bacterial clearance and causes lethality in mouse lung infection [27] . Considering that neutrophils are the most professional effect or cells against foreign pathogens, the capacity of KRT to promote bactericidal functions of neutrophils should be noted.…”
Section: Ly6gmentioning
confidence: 99%